Evaluating corneal cross-linking using Stress-Strain Index maps: a finite element study - Wang, Chenyan; Lou, Yuanwan; Ye, Yabo; Shen, Shuiyang; Bao, Fangjun; Wang, Junjie; Elsheikh, Ahmed (Journal of the Royal Society interface, 2025)
Keratoconus (KC) is a progressive corneal ectasia leading to visual impairment if untreated. Corneal collagen cross-linking (CXL) is an effective treatment to halt KC progression by strengthening corneal biomechanics. However, current CXL treatments lack customization based on regional corneal stiffness, which is crucial for optimal outcomes. This study introduces a novel approach using Stress-Strain Index (SSI) maps to evaluate localized CXL effects on corneal biomechanics. Numerical modelling based on the finite element method was used to carry out inverse analysis of the human eye to simulate KC and CXL treatments, incorporating regional stiffness variations based on collagen fibril density. SSI maps were generated pre- and post-CXL to assess stiffness changes in treated regions. Results demonstrated that CXL increased corneal stiffness within the treated area, but the extent of stiffness recovery varied with CXL diameter and alignment with the KC cone. Smaller CXL diameters led to higher localized stiffness increases, while misalignment between CXL and KC areas resulted in suboptimal biomechanical restoration. The study highlights the potential of SSI mapping for personalized CXL treatments, enabling precise targeting of biomechanically weakened regions to restore corneal health. This approach contributes to the development of biomechanics-based customization of CXL therapies.